ON SOME GROWTH PROPERTIES OF DIFFERENTIAL POLYNOMIALS IN THE LIGHT OF RELATIVE ORDERL - Datta, Sanjib Kumar; Biswas, Tanmay; Hoque, M.D. Azizul (Italian Journal of Pure and Applied Mathematics, 2014)
In the paper we establish some newly developed results based on the growth properties of relative order (relative lower order), relative type (relative lower type) and relative weak type of differential polynomials generated by entire and meromorphic functions.